Dismantling Descartes’ Cogito: Samuel Beckett’s Subversion of the Cartesian Subject in Endgame. - ALBAYRAK, Gökhan (Journal of Literature & Humanities / Edebiyat ve Beşeri Bilimler Dergisi, 2026)
This article examines Samuel Beckett’s Endgame as a profound theatrical subversion of the Cartesian model of subjectivity epitomized by the dictum cogito ergo sum. In a post-apocalyptic world where time has stalled, language has decayed, and relational structures have calcified into rituals of dependency, Beckett dismantles the notion of the autonomous, coherent, rational self. Instead, his fragmentary, immobile, and compulsively performative characters assert their existence not through thought but through speech acts, repetition, narrative, and power relations. The Cartesian cogito is refracted into a series of Beckettian counter-formulations: narro ergo sum, regno ergo sum, and ago ergo sum, each of which is a fragile and ironic mode of being within a void stripped of metaphysical assurance. Through close reading and textual analysis, this study explores how language functions not as a vehicle of meaning but as a bulwark against silence, how identity emerges through asymmetrical interdependence, and how memory, performance, and physical gestures serve as existential scaffolding for subjects in ontological crisis. Beckett’s drama thus offers a rigorous critique of Cartesian selfhood while staging a theatre of endurance in which the self is not discovered but incessantly fabricated in the face of erasure.